Конституційна природа права на доступ до правосуддя в Україні - Лужанський, А. В.; Лужанский, А. В.; Luzhanskyj, A. (My University, 2010)
The article is devoted to research of constitutional principles of access to justice in Ukraine, to ﬁ nding out of its legal nature. An author is ground a thesis that though right on access in a court is not envisaged at the level of Constitution of Ukraine interpreted literally, however it is such actually and in the context of component element of right of judicial defence it is assured by Basic Law of Ukraine. The necessity of ﬁ xing of the mentioned positive legal right by a material constitutional norm is marked.
Лужанський А. В. Конституційна природа права на доступ до правосуддя в Україні / А. В. Лужанський // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 57-63.
Keywords: конституційна природа права на доступ до правосуддя в Україні; гарантія судового захисту; конституционные принципы доступа к правосудию в Украине; гарантии судебной защиты; the constitutional principles of access to justice in Ukraine; guarantees of judicial protection